Effect of crumb rubber on the mechanical properties of crushed recycled pavement materials. (15th July 2018) - Li, Jie; Saberian, Mohammad; Nguyen, Bao Thach
Abstract: The low-carbon footprint of using recycled construction and demolition (C&D) aggregates in civil engineering infrastructure applications has been considered to be a significant solution for the replacement of conventional pavement aggregates. Investigations regarding the use of crumb rubber in the base and subbase layers of pavement have been well documented. However, information on the effects of crumb rubber and its size within C&D aggregates as the base/subbase layers is still very limited. In this study, crumb rubber with particle sizes ranging from 400 to 600 μm (fine) to 10–15 mm (coarse), 20 mm recycled crushed concrete (RCC), and 20 mm crushed rock (CR) were used. The crumb rubber was added to the two groups of C&D aggregates at 0.5, 1 and 2% by weight percentages of the aggregates. The effect of crumb rubber on the mechanical properties (such as California bearing ratio, unconfined compressive strength, aggregate crushing value, dynamic lightweight cone penetrometer, Clegg impact value, Los Angeles abrasion values, and resilient modulus) of the C&D aggregates was then examined. Based on the experimental test results, it was found that crumb rubber can be recycled as a waste material for the base and subbase layers in the pavement. Highlights: CBR increased with the fine rubber content but decreased when coarse rubber content was increased. The inclusion of both coarse and fine rubbers led to an increase in the deformability index and failure strain. The CIV of the aggregates decreased with the addition of both fine and coarse rubbers. DCPI decreased by increasing the fine rubber, however, it increased by increasing the coarse rubber. The resilient modulus decreased as the rubber content was increased.